The Challenges and Potential of Implementing Restorative Justice for Minor Criminal Offenses in Indonesia - Mimi; Muhamad Adystia Sunggara (Dinasti Research, 2025)
Indonesia, as a nation of law, faces challenges in integrating the restorative justice approach into the resolution of minor criminal offenses. This approach is considered more humane as it prioritizes the restoration of harm to victims and the accountability of offenders rather than mere punishment. This study aims to identify the main obstacles in the implementation of restorative justice, particularly in cases of minor criminal offenses, and to provide recommendations for improving its effectiveness. The research method employs a normative approach with an analysis of legal documents and related literature. The results of the study show that although restorative justice has been adopted in several policies, such as Attorney General Regulation Number 15 of 2020 and Police Regulations, its implementation is still hindered by regulatory factors, the capacity of law enforcement, public perception, limited resources, and local cultural dynamics. The conclusion of this study emphasizes the importance of integrated legal policy reform, continuous training for law enforcement, and public education about the benefits of this approach. By overcoming these obstacles, restorative justice has the potential to be an effective and inclusive solution in reforming Indonesia's criminal justice system.